A Personalized Model of COQ2 Nephropathy Rescued by the Wild-Type COQ2 Allele or Dietary Coenzyme Q10 Supplementation. - Zhu, J.Y.; Fu, Y.; Richman, A.; Zhao, Z.; Ray, P.E.; Han, Z. (Journal of the American Society of Nephrology, 2017)
Clinical studies have identified patients with nephrotic syndrome caused by mutations in genes involved in the biosynthesis of coenzyme Q10 (CoQ10), a lipid component of the mitochondrial electron transport chain and an important antioxidant. However, the cellular mechanisms through which these mutations induce podocyte injury remain obscure. Here, we exploited the striking similarities between Drosophila nephrocytes and human podocytes to develop a Drosophila model of these renal diseases, and performed a systematic in vivo analysis assessing the role of CoQ10 pathway genes in renal function. Nephrocyte-specific silencing of Coq2, Coq6, and Coq8, which are genes involved in the CoQ10 pathway that have been associated with genetic nephrotic syndrome in humans, induced dramatic adverse changes in these cells. In particular, silencing of Coq2 led to an abnormal localization of slit diaphragms, collapse of lacunar channels, and more dysmorphic mitochondria. In addition, Coq2-deficient nephrocytes showed elevated levels of autophagy and mitophagy, increased levels of reactive oxygen species, and increased sensitivity to oxidative stress. Dietary supplementation with CoQ10 at least partially rescued these defects. Furthermore, expressing the wild-type human COQ2 gene specifically in nephrocytes rescued the defective protein uptake, but expressing the mutant allele derived from a patient with COQ2 nephropathy did not. We conclude that transgenic Drosophila lines carrying mutations in the CoQ10 pathway genes are clinically relevant models with which to explore the pathogenesis of podocyte injury and could serve as a new platform to test novel therapeutic approaches.